2008
DOI: 10.1136/jech.2007.064212
|View full text |Cite
|
Sign up to set email alerts
|

Widening the scope, targeting interventions, creating risk groups: maternal and child health in Denmark and Sweden from 1930s and onwards

Abstract: The subject of this article is the health checks for pregnant women and children in Denmark and Sweden introduced in the 1930s and 1940s. It focuses on how political goals and means have changed up until today. The questions addressed are: Which health issues did the politicians and authorities find relevant to deal with? How should they be dealt with? Who were the interventions targeted towards? It is shown that from the 1970s changes gradually took place in two respects. (1) The scope widened inasmuch as inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Maternal and prenatal care in Denmark has changed considerably over the observation period included in our study. 32 Such changes may have had differential effects depending on whether a child was born into a family with lower rather than exceptional health at baseline. Overlapping birth cohorts between successive generations in our study allowed us to directly assess the intergenerational transmission of the observed survival advantages in restricted samples, without reference to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal and prenatal care in Denmark has changed considerably over the observation period included in our study. 32 Such changes may have had differential effects depending on whether a child was born into a family with lower rather than exceptional health at baseline. Overlapping birth cohorts between successive generations in our study allowed us to directly assess the intergenerational transmission of the observed survival advantages in restricted samples, without reference to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The vulnerable group can feel that their needs are recognized and therefore creating a starting point for improved communication and patient safety. However, the categorization can also negatively bias the health professional’s perception of this group and introduce stigma [22]. Link and Phelan define stigma as follows: “Stigma exists when elements of labeling, stereotyping, separation, status loss, and discrimination occur together in a power situation that allows them” [26].…”
Section: Discussionmentioning
confidence: 99%
“…The Danish ANC has been characterized as universal (all women are entitled to the same care), however, with increasing attention to identify and help women considered to be in special need [22]. Thus, introducing selective and targeted approaches and partly abolishing the universal welfare provision.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women and parents were target groups for extensive health education campaigns that aimed to change their behaviours (Vallgårda, 2003(Vallgårda, , 2008. Literature that gave advice on how to care for infants in order to keep them alive and healthy, however, has had a much longer history (Løkke, 1998: chapter 9).…”
Section: Focus On Health-related Behaviours Has a Long Historymentioning
confidence: 98%
“…Since the 1920s the Danish National Board of Health has published pamphlets in which breastfeeding is a central issue, for advising mothers on how to take care of their infants (Sundhedsstyrelsen, 1921(Sundhedsstyrelsen, , 1999. Pregnant women and parents were target groups for extensive health education campaigns that aimed to change their behaviours (Vallgårda, 2003(Vallgårda, , 2008. Literature that gave advice on how to care for infants in order to keep them alive and healthy, however, has had a much longer history (Løkke, 1998: chapter 9).…”
Section: Focus On Health-related Behaviours Has a Long Historymentioning
confidence: 99%